FEATURES OF SPEECH OF PERSONS WITH VISUAL IMPAIRMENTS - Rimbayeva Ozoda Bazarbayevna (Galaxy International Interdisciplinary Research Journal, 2024)
In individuals with developmental disabilities, one defect may become the cause of the second defect. Especially since our speech is formed on the basis of imitation, the fact that there is a defect in any of our cognitive activities will definitely affect our speech. In the following article, we will get acquainted with the features of speech of persons with a visual impairment.